Analisis Potensi Limbah Peternakan Sapi Potong Sebagai Penyedia Pupuk Organik Di Kecamatan Losarang Kabupaten Indramayu - Rastono; Oki Imanudin; Dini Widianingrum (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2023)
This research was conducted at the Banteng Tani Livestock Group, Losarang District, Indramayu Regency from February 20 to March 30, 2022. This study aims to analyze the potential of beef cattle farm waste in providing organic fertilizer needs for the community in Losarang District, Indramayu Regency. This study uses a descriptive method that is analyzing the cost efficiency of organic fertilizer production using R/C ratio analysis. The results of the feasibility analysis of farming using the balance of revenues and costs (R/C ratio) with a value of 1.84. This means that each expenditure of Rp. 1 will generate revenue of Rp. 1.84. The coefficient value of the R/C ratio shows a number more than 1, so it can be concluded that the use of costs in the organic fertilizer production process in the Banteng Tani group is efficient.